Dexamethasone pulse therapy in patients of systemic sclerosis: Is it a viable proposition? A study from kashmir - Sameem Farah; Hassan Iffat; Ahmad Qazi; Khan Dilshad; Majeed Imran; Kamili M; Shah Parvaiz (Wolters Kluwer Medknow Publications, 2010)
Background: Systemic sclerosis is a multisystemic autoimmune disorder. Intravenous dexamethasone pulse therapy has been used since 1998. Aim: The aim was to report the beneficial effects of dexamethasone pulse in patients of systemic sclerosis vis-á-vis the side effects. Materials and Methods: Forty-seven patients of systemic sclerosis were included. After looking at the history and physical examination, the patients were submitted to various relevant investigations. Clinical scoring of the patient was done at baseline and 6-month interval according to Furst′s organ indices score. Results: A total of 47 patients of systemic sclerosis were included (45 females, 2 males). In majority, acrosclerosis was seen. Severe sclerosis and contractures were seen in two patients. Moderate proteinuria, restrictive lung disease, dysphagia, and valvular heart involvement were seen. A total of 13 patients on dexamethasone pulse therapy developed tuberculosis. Improvement in skin scoring and decreased severity of Raynaud′s phenomenon was seen. No improvement in dysphagia, severe vascular symptoms, or restrictive lung disease was seen. Conclusion: Thus, beneficial effects of dexamethasone pulse therapy seem to be merely cosmetic.